LEGENDA LIANG SIPEGE DI DESA SIMARMAR PEATALUN HUTAGAOL KECAMATAN BALIGE KABUPATEN TOBA : KAJIAN SOSIOLOGI SASTRA - Silaen, Batara Gomal; Sinaga, Warisman (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This article discusses the Legend of Liang Sipege. The problem in this research is the Intrinsic Element  The Legend of Liang Sipege, The Sociological Values ​​of Literature contained in the Legend of Liang Sipege  and Community Views on the Legend of Liang Sipege. The legend of Liang Sipege is  one form of story that belongs to the Toba Batak community, which is precisely located in the village of  Simarmar Peatalun Hutagaol, Balige District, Toba Regency. This research aims to  knowing the structure of the story and knowing the Sociological Values ​​of Liang Sipege's Literary Legend.  The arrangement of stories and events that occur in the Legend of Liang Sipege story is structured and organized  translate it into a story and explore the cultural values ​​in it. The method used  used to analyze this research problem is the qualitative method with the  field. This study uses structural theory and the theory of the Sociology of Literature. The intrinsic elements in this story include: theme, plot or plot, background or setting, and  character or characterization